Hubungan Pengetahuan Dengan Sikap Ibu Hamil Tentang Pemeriksaan Triple Eliminasi Di Puskesmas Arjowinangun - Avelia Renova Avidatun Nisa'; Ni Wayan Dwi Rosmalawati; Duhita Dyah Apsari (Madu Jurnal Ilmu Kebidanan, 2026)
The rate of transmission of infectious diseases from mother to child such as HIV, Syphilis and Hepatitis B in Indonesia is still high. This group of infections is the main threat of congenital infections during pregnancy which can cause abnormalities in the fetus. In 2016, the World Health Organization (WHO) created a strategy program to prevent the transmission of infectious diseases from mother to child, known as Triple Elimination. Several factors that influence triple elimination examinations are the knowledge and attitudes of pregnant women in carrying out triple elimination examinations. research is to determine the relationship between knowledge and attitudes of pregnant women regarding triple elimination examinations at the Arjowinangun Community Health Center, Malang City. The research method is correlational analysis with a cross-sectional approach. The population in this study is the average number of pregnant women who visited ANC in January-March 2024, namely 90 pregnant women. Samples were taken using Consecutive sampling totaling 36. The research instrument used a questionnaire. Primary data collection. The statistical test uses the Spearmen Rank with a p-value < (0.05), meaning that there is a relationship between the knowledge and attitudes of pregnant women and the Triple Elimination examination. The results of this research showed that the knowledge variable had a p-value < 0.001, the attitude variable had a p-value < 0.001. There is a relationship between the knowledge and attitudes of pregnant women and the Triple Elimination examination in the working area of the Arjowinangun Community Health Center, Malang City.